Tillage and mulching effects on physical properties of a tropical alfisol - Franzen, H.; Ehlers, W. (Elsevier, 1994)
The mechanization of field operations like seeding, spraying and harvesting in continuous zero-tillage may lead to a severe compaction of the surface layer of coarse textured tropical soils, especially when mulch is sparse or missing. Therefore, a 2 year (1982–1984) field experiment was initiated on an Alfisol in Nigeria to study the effect of tillage, mechanization and mulch on soil structure and physical properties. Three zero-tillage treatments and a plough treatment were compared. The disk-plough and one of the no-till treatments were highly mechanized: all the field work was performed with tractors and machines, and consisted of secondary bush clearing, crop cultivation and harvest. On the other two no-till treatments, the impact of machine load was reduced, wither by hand harvesting or by performing all field operations manually. These four tillage-traffic systems were either treated with mulch or left unmulched. There were four growing seasons, with maize (Zea mays L.) as a test crop. After 2 years of zero-tillage the bulk density (BD) and penetration resistance (PR) were significantly greater on plots with high mechanization compared with hand treated plots. Plots with hand harvest but otherwise mechanized were in between. Because of the hard-setting nature of the soil, the ploug heed plots with and without mulch exhibited a dramatic change in PR and BD during the season. On no-till the infiltration transmissivity (A) was greater and BD and PR were less in the mulched compared with the unmulched treatments. The gravel content of the topsoil was negatively correlated with BD and positively correlated with A. Geostatistical analysis revealed that within the experimental area there was a similar spatial distribution of gravel content and A after the first season. Because of the superimposing effect of gravel on BD, which cannot be accounted for by considering the gravel content per se, BD was adjusted by means of covariance analysis for evaluation of the treatment effects already mentioned. It was concluded that mechanization of a no-till system on sandy Alfisols may only be successful in the long run if appropriate measures like mulching, crop rotation and fallow systems are applied to regenerate soil structure and to enhance macroporosity.